Rol de enfermería en pacientes hipertensos de 50 a 75 años de edad que acuden al Dispensario el Pambilar de Calope del Seguro Social Campesino del cantón Quinsaloma, provincia de Los Ríos, en el primer semestre del 2013 - Alarcón Alarcón, Clelia René (2013)
Hypertension (HTA) is, worldwide, the leading cause of death due mainly to its high prevalence in the population as a cardiovascular risk factor, besides being the main risk factor for coronary heart disease, which turn is the leading cause of death worldwide This research aims to determine the role of nursing in hypertensive patients 50-75 years of age attending the Dispensary The Pambilar De Calope Rural Social Insurance Quinsaloma from Canton, Province De Los Rios in the first half of 2013. In addition, look for: Identify the risk factors affecting the increase in blood pressure in hypertensive patients 50-75 years of age attending the Dispensary Pambilar To study the levels of involvement occurs more frequently in patients with a diagnosis of hypertension from 50 to 75 years old attending the Dispensary Pambilar Make a nutritional guide for hypertensive patients 50-75 years of age attending the Dispensary Pambilar The methods used in this research are of type, inductive and deductive, analytic and synthetic, which makes the research more understandable and analytical